Understanding state welfare : social justice or social exclusion? - Lund, Brian, 1945- (SAGE, 2002)
Lund (Manchester Metropolitan U.) explores some of the theories and principles underlying the government provision of services whether in the narrow US sense of emergency and temporary aid or the broader European sense that includes such permanent services as health care and housing.